Effectiveness evaluation of two volumizing hyaluronic acid dermal fillers in a controlled, randomized, double-blind, split-face clinical study - Kerscher M; Agsten K; Kravtsov M; Prager W (Dove Medical Press, 2017)
Martina Kerscher,1 Karla Agsten,2 Maria Kravtsov,3 Welf Prager4 1Department of Cosmetic Science, University of Hamburg, 2SCIderm GmbH, Hamburg, Germany; 3Anteis S.A., Geneva, Switzerland; 4Prager & Partner Dermatologische Praxis, Hamburg, Germany Background: Enhancement of the midface can be achieved with volumizing hyaluronic acid (HA) fillers.Objective: The objective of this study was to compare the safety and effectiveness of Cohesive Polydensified Matrix® 26 mg/mL HA gel (CPM-26) and Vycross® 20 mg/ml HA gel (VYC-20) in a controlled, randomized, evaluator-blind, split-face clinical study.Patients and methods: Subjects with moderate-to-severe malar volume loss on the Merz Aesthetics Scale (MAS) received CPM-26 on one side and VYC-20 on the contralateral side of the face. Effectiveness assessments were performed by blinded evaluators including photographic and live MAS ratings and live Global Aesthetic Improvement Scale (GAIS) ratings. Calculations of anatomical volume variations at month 3 (M3), month 6 (M6), month 12 (M12) and month 18 (M18) were also performed.Results: Non-inferiority of CPM-26 versus VYC-20 was demonstrated at M3 (primary end point) based on MAS. GAIS rating showed that significantly more subjects had better improvement with CPM-26 than with VYC-20 at month 1, M3, M12 and M18 (p=0.0032, p=0.0074, p=0.0384 and p=0.0110, respectively). Standardized evaluation of volume variations from baseline to M3, M12 and M18 showed that CPM-26 created more volume augmentation at all time points, and the difference was significant at M3.Conclusion: CPM-26 was non-inferior to VYC-20 based on MAS ratings at M3 and demonstrated a favorable safety and effectiveness profile for midfacial volume enhancement with results lasting up to M18. Keywords: cohesive polydensified matrix, hyaluronic acid fillers, Belotero® Volume, Modélis® SHAPE, Juvéderm® VOLUMA®, volumizing